COUNTRY-BY-COUNTRY REPORTING OF LEADING EU-UKRAINE FORESTRY COMPANIES: ENVIRONMENTAL CAPITAL DISCLOSURE COMPARATIVE STUDY - Zhanna Oleksich; Roman Fominov (Соціальна економіка)
This study aims to analyze the activities of forestry companies in both the European Union countries and Ukraine through an examination of their non-financial reports. By scrutinizing these reports, the study seeks to unveil aspects of social responsibility and assess the degree of implementation and achievement of Sustainable Development Goals. Special attention is given to the disclosure of ecological information by forestry enterprises, aimed at identifying potential risks and enhancing investor and consumer trust. The article underscores the significance of ecological responsibility within the strategies and operations of these companies. It highlights the sustainability report as a pivotal tool for modern forestry firms, fostering improved management practices, collaboration, and development based on sustainability principles. The push for non-financial information disclosure, driven by EU Directives, incentivizes enterprises to refine their strategies, incorporating ecological and social considerations and fostering responsible conduct towards stakeholders. The authors conduct an in-depth analysis of transparency levels, ecological responsibility, and the extent to which ecological aspects are integrated into the operations of forestry enterprises. Companies that effectively implement and expand non-financial reporting in the forestry and wood processing sectors are better positioned to attract investments from funds and consumers prioritizing sustainability and ethics. Consequently, this fosters a positive public perception and enhances competitiveness. The relevance of this research lies in its contribution to environmental preservation and the establishment of a sustainable economy. The findings are expected to provide valuable insights into environmental management practices and guide efforts towards enhancing ecological sustainability in forestry.